INTERNALISASI NILAI-NILAI KEASWAJAAN DI SMA HASYIM ASY’ARI KOTA BATU - Amirudin Amirudin; Mohammad Afifulloh; Imam Safi’i (VICRATINA, 2021)
Aswaja values are values to be applied and integrated into the life of a character that is tawasut, tawazun, tasamuh and ta'adul. Hasyim Asy'ari High School is a school under the auspices of Nahdlatul Ulama, which in the learning process teaches a lot of private values. This study will discuss the forms of activities, processes, and impacts of the internalization of Aswaja values at SMA Hasyim Asy'ari Batu City. The method in this study uses a qualitative approach with the type of case study research. In collecting data the researchers used interview, observation, and documentation techniques. From the results of the study, it was found that the form of internalization of Aswaja values at SMA Hasyim Asy'ari was divided into daily, weekly, and annual activities. The process is formed in an Aswaja-based learning system. And this has the impact of realizing a culture of tawassuth, tawazun, i'tidal among students..     Kata Kunci: Internalisasi, Nilai-Nilai, Keaswajaan.